Immunohistochemical localisation of advanced glycation end products in pulmonary fibrosis. Issue 7 (July 1998) - Matsuse, T; Ohga, E; Teramoto, S; Fukayama, M; Nagai, R; Horiuchi, S; Ouchi, Y
Abstract : AIM: To investigate the presence and distribution of advanced glycation end products (AGE) in pulmonary fibrosis. METHODS: Lung tissue samples obtained from seven necropsy cases with idiopathic pulmonary fibrosis and seven with normal pulmonary parenchyma were examined immunohistochemically with a monoclonal antibody specific for AGE: 6D12. We also tested three cases with diffuse alveolar damage. RESULTS: All the specimens from cases with pulmonary fibrosis and diffuse alveolar damage showed strong AGE expression on macrophages. Lung specimens from normal parenchyma showed positive AGE immunoreactivity on macrophages from only two of seven cases. CONCLUSIONS: These findings suggest that AGE modified proteins accumulate in alveolar macrophages in patients with diffuse alveolar damage and idiopathic pulmonary fibrosis.